Relavance of peritoneal drainage fluid lactate level in patients with intra-abdominal hypertension - Natasa Kovac; Mladen Siranovic; Mladen Peric (Cogent Medicine, 2017)
Objective: The aim of this study was to assess the effect of intra-abdominal hypertension (IAH) on peritoneal fluid lactate, local and systemic organ dysfunctions in patients after major abdominal surgery. Methods: In this prospective study, 26 patients were followed in the surgical intensive care unit. The lactate in peritoneal drainage fluid was analyzed 24 h after surgery concurrently with diuresis, renal FG, APP, creatinine clearance, bilirubin, AST, ALT, prothrombin time, CVP, cardiac index, PaO2, BE, arterial pH, arterial lactate, ScvO2, FiO2/pO2 ratio, oxygen delivery, MAP and APACHE II. In the procedure 1 ml of peritoneal drainage fluid was drawn out from drainage catheter placed in abdominal cavity at the end of the operation. IAH has been defined as a peak intra-abdominal pressure (IAP) value of ≥12 mm Hg, at a minimum, as two standardized measurements obtained 1–6 h apart. Results: There were 16 patients with IAP > 12 mm Hg and 10 patients with IAP < 12 mm Hg. The mean IAP in groups was 18.02 ± 7.00 vs. 8.00 ± 1.80 mm Hg, p < 0.05, respectively. There are three major findings: a selective sensitivity of various organs dysfunction to the IAH level; the increase of IAP leads to lactate hyperproduction in abdominal drainage fluid (12.60 vs. 9.90 mmol/L, p < 0.05; and the systemic oxygen delivery was unaltered despite worsening of the local and systemic parameters caused by IAH. Conclusion: The lactate level in peritoneal drainage fluid may be an indicator of intra-abdominal dysfunction in surgical patients with IAH. Clinical monitoring of local lactate production may have a potential predictive and prognostic value.